SOCIAL RETURN ON INVESTMENT (SROI) UNDER THE RESEARCH PROJECT ON INCREASING THE CAPACITY OF COMMUNITY BUSINESSES AND OPPORTUNITIES SOCIETY UNDER APPROPRIATE TECHNOLOGY FOR LOCAL FISHERY GROUPS PATTANI PROVINCE - Suraban, Paweekorn; Makchura, Chidchanok; Sani, Suhaidee (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This study aims to assess the Social Return on Investment (SROI) of a research project on empowering community businesses and social opportunities under appropriate technology, focusing on analyzing the economic, social, and environmental impacts on target groups in three districts of Pattani Province: Yaring, Panare, and Nong Chik districts. The population used in this study was purposive sampling. The project participants were local fishermen, fish raft owners, and members of local seafood processing groups, totaling 258 people. The data collection tools included focus group discussions and structured interviews, along with economic research methods to calculate the social return on investment (SROI). The study found that the research project had a positive impact on multiple dimensions. For Economic aspect, it was found that household income increased, sales increased, and production costs decreased. For social aspect, it was found that participants experienced improved physical and mental health, increased knowledge, fostered greater cooperation, love, and unity within the group, and reduced healthcare costs for work-related illnesses. For environmental aspect, it was found that participants reduced energy consumption and waste management costs from waste cloth scraps, and were better able to manage this waste problem. The project's return on investment (SROI) analysis found an SROI of 1.19, meaning that for every 1 baht invested, 1.19 baht of social value was generated. This demonstrated that the project is cost-effective and can benefit communities and society in the long term.